Time-domain signal analysis of dielectric response of nonlinear SDBD thruster in near space. (January 2023) - Liwei, Zhou; Liqiu, Wei; Zhou, Yang; Changyou, Suo; Jingjing, Li; Desheng, Zhou; Yongjie, Ding; Hong, Li; Jingfeng, Tang
Abstract: The nonlinear time domain response signals of surface dielectric barrier discharge (SDBD) are the basis for studying the energy loss of SDBD thruster. This paper is based on the construction of a double layer lumped parameter circuit model in solid dielectric and discharge plasma regions; based on virtual instrument technology, a test device for AC dielectric characteristics of a nonlinear SDBD thruster was built to obtain the time domain signals of AC voltage and response current. According to the characteristic spectral curve of the voltage and the response current signal in the time domain, the response current is decomposed into resistive current (conduction current) and capacitive current (relaxation current) by an appropriate algorithm. The experimental results show that the response current in the discharge plasma region is mainly the capacitive current, and the peak capacitive current is about 2.9 times of the peak resistance current; Relaxation planned loss is the main form of energy loss in the discharge plasma region. Due to space charge limiting current effect and space charge saturation effect, the static and dynamic resistance of discharge plasma region have platform area and negative resistance characteristics respectively; Both static and dynamic capacitance have negative capacitor characteristics. Highlights: This paper is based on the construction of a double layer lumped parameter circuit model in solid dielectric and discharge plasma regions; based on virtual instrument technology, a test device for AC dielectric characteristics of a nonlinear SDBD actuator was built to obtain the time domain signals of AC voltage and response current. The response current is decomposed into resistive current (conduction current) and capacitive current (relaxation current) by an appropriate algorithm. By analyzing the response current waveform, static and dynamic time domain characteristic curves of resistance and capacitance in the plasma region of the SDBD actuator were obtained. The discharge characteristics of the plasma region of the SDBD actuator are characterized more comprehensively.